Preparation method of separation material filled with metal pi site MOF and application of separation material in carbon capture
By using the physical blending technology of Mx-MOF-808 material with metal π site structure and Pebax polymer matrix, a hybrid matrix membrane capable of selective recognition in CO2/CH4 separation was prepared, and the prior art was solved. The problem of insufficient selective recognition ability of fill materials has significantly improved the separation performance.
Patent Information
- Application Number
- CN202411846780.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-11
AI Technical Summary
Existing mixed matrix membranes (MMMs) lack effective fill materials that can selectively identify carbon dioxide in CO2/CH4 separation, resulting in limited separation performance.
Using Mx-MOF-808 material with metal π site structure as filler, combined with polyether polyimide block Pebax as polymer matrix, prepare a mixed matrix membrane through physical blending, and use metal-π interaction to achieve CO2 selective identification.
The selection and permeability of CO2/CH4 in the membrane are improved, and the selectivity and CO2 flux of CO2/CH4 are significantly improved, which is better than the existing technology.
Smart Images

Figure HDA0005189423660000011 
Figure HDA0005189423660000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation and carbon capture, and in particular relates to a method for preparing a separation material filled with metal π sites MOF and its application in carbon capture. Background Art
[0002] Biogas is an energy-dense, renewable fuel that is considered a promising alternative to natural gas. However, the presence of CO2 significantly reduces the calorific value of biogas. In addition, CO2 is considered a major contributor to the greenhouse effect. In this context, pre-capture of CO2 from biogas is critical for both improving biogas quality and mitigating climate change. Among various upgrading technologies, membrane separation technology has attracted much attention due to its relatively low energy consumption and compact footprint. Efficient membrane materials are essential for efficient membrane-based biogas upgrading. Among various separation membranes, mixed matrix membranes (MMMs) stand out due to their porous filler composition in a polymer matrix. This combination takes advantage of the easy processing properties of polymers and the high separation performance of fillers and has therefore been proven to be effective for CO2 / CH4 separation. However, a key limitation in achieving efficient separation using MMMs is the lack of effective filler materials that can selectively recognize carbon dioxide, which is essential to maintain high separation performance.
[0003] Metal-organic frameworks (MOFs) have attracted much attention as filler materials due to their highly engineered structures and functions, standing out among many options. Although many MOF materials have enhanced their affinity for CO2 by increasing the number of basic sites or introducing specific functional groups, they still face the challenge of achieving selective recognition of CO2 in MMMs. Undoubtedly, traditional intermolecular interactions (hydrogen bonds, van der Waals forces, and electrostatic interactions) pose significant challenges to achieving selective recognition of CO2 when developing MMMs. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing a separation material having a metal π site MOF filling and its application in carbon capture. The present invention first prepares a separation material having a metal π site structure MOF filling. x -MOF-808 material, and used it as a filler to prepare a mixed matrix membrane; the mixed matrix membrane is composed of M x -MOF-808 is used as a filler and polyether polyimide block Pebax is used as a polymer matrix. The mixed matrix membrane is formed by physically blending the filler and the polymer matrix at room temperature; the carbon capture material improves the selectivity and permeability of CO2 / CH4 in the membrane, has good selectivity for CO2 / CH4, and can be used to separate CO2 / CH4.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:
[0006] The present invention first provides a metal π site structure M x -MOF-808 material, characterized in that the MOF with metal π sites synthesizes a series of MOF-808 (Mx-MOF-808) fillers containing unsaturated Zr sites by competitive coordination replacement method; the material has metal π sites, and the metal π site density is M 50 -MOF-808>M 30 -MOF-808>M 10 -MOF-808.
[0007] The present invention also provides a method for preparing the Mx-MOF-808 having a metal π site structure, which specifically comprises the following steps:
[0008] S1. Zirconium oxychloride octahydrate (ZrOCl2·8H2O), trimesic acid (H3BTC), and benzoic acid (HBC) in different molar ratios (10%, 30%, and 50%) were added to a Teflon-lined reactor (100 mL) to replace an equal amount of H3BTC. During the synthesis, HBC competes as a temporary ligand for coordination with the Zr cluster. Then a mixed solvent of N,N-dimethylformamide (DMF) / formic acid (HCOOH) was added. Next, the reactor was sealed and stirred for 0.5 hours to obtain a uniform mixed solution. The reactor was then transferred to a drying oven in an oven and kept at a certain temperature for several hours. After cooling to room temperature, the reaction product was washed with DMF and MeOH and centrifuged to separate the white precipitate. Then, the solid product was immersed in methanol (MeOH) for three days (MeOH was replaced every day), and a white precipitate was obtained after centrifugation. The white powder was obtained after being placed in a vacuum drying oven at 80°C overnight and named M x -MOF-808.
[0009] The M having a metal π site structure x - A method for preparing MOF-808 material, characterized in that the M in step S1 x - In MOF-808, the dosage of ZrOCl2·8H2O, H3BTC and HBC is in the following relationship: 0.70-0.75g: 0.45-0.5g: 10-50%;
[0010] The M having a metal π site structure x -The preparation method of MOF-808 material is characterized in that, in step S1, the volume ratio of DMF to HCOOH is 25-30mL:25-30mL.
[0011] The experimental conditions in S1 were heating with stirring at 25-30°C for 0.5-1 h.
[0012] The experimental conditions for immersing the product in methanol in S1 are 50-100 mL, displacing in methanol for 3-5 days, and heating and drying in an oven at 75-90°C for 24-30 hours.
[0013] The M having a metal π site structure x -Application of MOF-808 materials in the preparation of carbon capture materials.
[0014] A method comprising the M having a metal π site structure as claimed in claim 1 x -MOF-808 carbon capture material preparation method, characterized in that the carbon capture material is the M having a metal π site structure x -MOF-808 material is a filler, polyether polyimide block Pebax is a polymer matrix, and the carbon capture material is formed by physically blending the filler and the polymer matrix at room temperature; the mass percentage of the filler in the carbon capture material is 1 to 15wt%.
[0015] The present invention also provides a method for preparing the above carbon capture material, which specifically comprises the following steps:
[0016] (1) dissolving a polyether polyimide block Pebax in a mixed solution of ethanol and water to obtain a polyether polyimide block Pebax solution;
[0017] (2) The above-mentioned metal π site structure M x -The carbon capture material of MOF-808 is physically blended with the polyether polyimide block Pebax solution and stirred at room temperature to obtain a casting solution;
[0018] (3) Casting and drying the casting solution to obtain the carbon capture material.
[0019] Preferably, the carbon capture material has a metal π site structure M x -The filler of MOF-808 accounts for 1% to 14% of the mass percentage of the carbon capture material.
[0020] The present invention also provides application of the above carbon capture material in carbon capture.
[0021] Preferably, the application includes: separation of CO2 / CH4 mixed gas.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The metal π site structure M prepared by the present invention x -MOF-808 material; the M x-MOF-808 material has metal π sites with a metal π site density of M 50 -MOF-808>M 30 -MOF-808>M 10 -MOF-808. x -MOF-808 material has a high metal π site structure, which constructs a dedicated transport path for CO2 with low mass transfer resistance in MMMs. The present invention proposes a potential solution based on molecular orbital differences. Considering the significant differences in the molecular orbitals of CO2 and CH4, the CO2 molecule has an unoccupied π* antibonding orbital, while the saturated hydrocarbon CH4 has no unoccupied π orbital. This difference provides an opportunity for the selective separation of CO2 through metal-π interactions. We propose a new design concept to achieve selective recognition of carbon dioxide in MMMs by designing MOF fillers with specific metal-π sites. The unsaturated metal sites in the MOF pores can selectively recognize CO2 molecules through metal-π interactions. In contrast, since CH4 molecules do not have metal-π interactions, they are blocked from entering the MOF pores. Therefore, CO2 / CH4 can be effectively separated in MMMs by utilizing the differences in metal-π interactions between CO2 and CH4.
[0024] The metal π site structure M of the present invention x -MOF-808 material forms a unique selective recognition channel within MMMs, further increasing the selectivity of the prepared carbon capture material for CO2 / CH4.
[0025] The present invention uses a polyether-polyamide block copolymer (Pebax) as a matrix containing a metal-π structure M x -MOF-808 carbon capture material builds an efficient CO2 transport channel in the membrane, containing metal-π structure M x -MOF-808 carbon capture material improves the permeation-selectivity performance of MMMs and overcomes the trade-off effect.
[0026] The carbon capture material of the present invention has a simple preparation process, controllable reaction, cheap and readily available raw materials, mild conditions, and can promote the complementary advantages of fillers and polymer matrices. x -MOF-808 carbon capture material has a maximum permeability selectivity of 1483.7 barrer for CO2 / CH4 mixed gas, and a CO2 / CH4 selectivity of 36.1, which is better than the existing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is M x-Transmission electron microscopy images of MOF-808: (a) MOF-808, (b) M 10 -MOF-808, (c)M 30 -MOF-808 and (d)M 50 -MOF-808.
[0028] Figure 2 It is Pebax / M 30 -SEM cross-sectional images of MOF-808: (a) Pebax / MOF-808-1MMMs, (b) Pebax / MOF-808-1MMMs 10 -MOF-808-4MMMs, (c)Pebax / M 30 -MOF-808-7MMMs, (d)Pebax / M 50 -MOF-808-10MMMs. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0030] Example 1: With metal π site structure M 10 - Preparation of MOF-808 materials
[0031] 0.73 g ZrOCl2·8H2O, 0.49 g H3BTC, and 10% molar ratio HBC were added to a 100 mL Teflon-lined reactor to replace an equal amount of H3BTC. During the synthesis, HBC competes as a temporary ligand for coordination with the Zr cluster. Then a mixed solvent DMF / HCOOH (60 mL, 30 mL / 30 mL) was added. Next, the reactor was sealed and stirred for 0.55 hours to obtain a uniform mixed solution. The reactor was then transferred to a drying oven in an oven and kept at 120 ° C for 25 hours. After cooling to room temperature, the reaction product was washed with DMF and MeOH and centrifuged to separate the white precipitate. The solid product was then immersed in 50 mL MeOH for three days (MeOH was replaced every day), and a white precipitate was obtained after centrifugation. The white powder was obtained after being placed in a vacuum drying oven at 80 ° C overnight and named M 10 -MOF-808.
[0032] Figure 1 M x -SEM images of MOF-808 (a) MOF-808, (b) M 10 -MOF-808, (c)M 30 -MOF-808 and (d)M 50 -MOF-808. Figure 1 It can be seen that M10 -The surface of MOF-808 material has obvious pores generated inside the material compared to MOF-808. The appearance of pores will spread more abundant unsaturated metal sites inside the pores.
[0033] from Figure 1 It can be seen that MOF-808 has a regular octahedral morphology with an average size of 0.5 μm. x -The morphology of MOF-808 was changed, which indicates that M x -MOF-808 was synthesized.
[0034] Example 2: With metal π site structure M 30 - Preparation of MOF-808 materials
[0035] 0.75 g ZrOCl2·8H2O, 0.50 g H3BTC, and 30% molar ratio HBC were added to a 100 mL Teflon-lined reactor to replace an equal amount of H3BTC. During the synthesis, HBC competes as a temporary ligand for coordination with the Zr cluster. Then a mixed solvent DMF / HCOOH (60 mL, 30 mL / 30 mL) was added. Next, the reactor was sealed and stirred for 0.52 hours to obtain a uniform mixed solution. The reactor was then transferred to a drying oven in an oven and kept at 120 ° C for 26 hours. After cooling to room temperature, the reaction product was washed with DMF and MeOH and centrifuged to separate the white precipitate. The solid product was then immersed in 80 mL MeOH for three days (MeOH was replaced every day), and a white precipitate was obtained after centrifugation. The white powder was obtained after being placed in a vacuum drying oven at 80 ° C overnight and named M 30 -MOF-808.
[0036] from Figure 1 It can be seen that M 30 -MOF-808 compared to M 10 -MOF-808 has more pores with an average size of 0.5 μm. 30 -The morphology of MOF-808 was changed, which indicates that M 30 -MOF-808 was synthesized.
[0037] Example 3: Containing metal π site structure M 10 -Preparation of carbon capture materials based on MOF-808
[0038] Weigh 0.551g 1657 was dissolved in 10 mL of a mixed solution of ethanol and water in a mass fraction ratio of 7:3, and heated and stirred in a water bath at 85° C. for 4 h to dissolve all the Pebax particles, thereby preparing a Pebax matrix solution with a mass fraction of 7 wt %.
[0039] Take 0.0398g of M prepared in Example 1 10 -MOF-808 is physically blended with the Pebax matrix solution, stirred at room temperature for 10 hours to obtain a casting solution, the casting solution is poured onto a clean culture dish for casting, and then dried at room temperature (25°C) for 50 hours. After drying, the residual solvent on the surface is removed to obtain the carbon capture material containing the metal π site structure.
[0040] According to M 10 -MOF-808 in the carbon capture material containing metal π-site structure has a weight percentage of 7%, denoted as Pebax / M 10 -MOF-808-7. After testing, the Pebax / M 10 -The thickness of MOF-808-7 is 108 μm.
[0041] In this embodiment, Pebax / M 10 -MOF-808-7 is used for CO2 / CH4 mixed gas separation test. The specific test conditions are:
[0042] Pebax / M 10 -MOF-808-7 was placed in a stainless steel membrane pool, and the flow rates of the raw gas (CO2 / CH4 mixed gas, the volume ratio of CO2 to CH4 was 2:8) and the purge gas (H2) were set to 50mL / min and 30mL / min respectively; the system temperature of the test instrument was 25°C, the pressure of the raw gas pressure regulating valve was 0.2Mpa, the raw gas was humidified by the gas humidification tank, and then the gas was dehumidified by the dehumidification tank, and the water content in the gas reached saturation. Finally, the permeate side gas was purged with hydrogen, and passed into the gas chromatograph to detect the composition and content of the permeate side gas, and the CO2 / CH4 separation performance of the mixed matrix membrane was calculated.
[0043] The test results show that the Pebax / M 10 -The CO2 flux of MOF-808-7 is 1476.2 barrer (1 barrer = 10 -10 cm 3 cm / cm 2 s cmHg), and the CO2 / CH4 selectivity was 36.9, far exceeding the Robeson upper limit in 2018.
[0044] Example 4: Containing metal π site structure M 30-Preparation of carbon capture materials based on MOF-808
[0045] Take 0.0472g of M prepared in Example 2 30 -MOF-808 is physically blended with 10wt% Pebax matrix solution, stirred at room temperature for 5 hours to obtain a casting solution, the casting solution is poured on a clean culture dish for casting, and then dried at room temperature (25°C) for 48 hours. After drying, the residual solvent on the surface is removed to obtain the carbon capture material containing the metal π site structure.
[0046] According to M 30 -MOF-808 in the carbon capture material containing metal π-site structure has a weight percentage of 10%, denoted as Pebax / M 30 -MOF-808-10. After testing, the Pebax / M 30 -The thickness of MOF-808-10 is 109 μm.
[0047] Figure 2 (d) is the obtained Pebax / M 30 -SEM cross-section of MOF-808-10. Figure 2 (d) It can be seen that M 30 -MOF-808 introduced into Pebax matrix contains metal π site structure M 30 -MOF-808 is evenly distributed on the cross-section of the carbon capture material without obvious agglomeration.
[0048] This example uses the method described in Example 3 to test Pebax / M at 25°C and 2 bar. 30 -MOF-808-10 has a good separation effect on CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. The CO2 flux is 1231.5 barrer and the CO2 / CH4 selectivity is 31.6, which is 90% higher than that of pure Pebax membrane and 30% higher in selectivity.
[0049] Example 5: Containing metal π-site structure M 50 -Preparation of carbon capture materials based on MOF-808
[0050] Take 0.0309g of prepared M 50 -MOF-808 is physically blended with 7wt% Pebax matrix solution, stirred at room temperature for 4 hours to obtain a casting solution, the casting solution is poured on a clean culture dish for casting, and then dried at room temperature (25°C) for 48 hours. After drying, the residual solvent on the surface is removed to obtain the carbon capture material containing a positive electrostatic potential microenvironment.
[0051] According to M 50-MOF-808 contains metal π site structure 50 -MOF-808 carbon capture material has a weight percentage of 7%, denoted as Pebax / M 50 -MOF-808-7. After testing, the Pebax / M 50 -The thickness of MOF-808-7 is 105 μm.
[0052] This example uses the method described in Example 3 to test Pebax / M at 25°C and 2 bar. 50 -MOF-808-7 has a CO2 / CH4 mixed gas separation effect. The CO2 flux is 672 barrer and the CO2 / CH4 selectivity is 20.8.
[0053] Comparative Example 1:
[0054] For comparison, 0.524 g of Pebax particles were weighed and dissolved in a mixed solution of 70% ethanol / 30% water by mass. After stirring at 80°C for 2 hours, the resulting casting solution was poured onto a clean ultra-flat surface dish and cast. It was dried at room temperature (25°C) for 48 hours and then placed in a vacuum oven at 40°C for 24 hours to remove the residual solvent, thereby obtaining a Pebax film with a thickness of 104 μm.
[0055] At 25°C and 2 bar, the Pebax membrane was used to separate a CO2 / CH4 mixed gas (the volume ratio of CO2 to CH4 was 2:8) with a CO2 volume fraction of 20%. The CO2 flux was 434 barrer and the CO2 / CH4 selectivity was 19.
[0056] In summary, the carbon capture material of the present invention has a simple preparation process, controllable reaction, cheap and readily available raw materials, mild conditions, and can promote the complementary advantages of fillers and polymer matrices. The carbon capture material containing a metal π site structure prepared by the present invention has a maximum CO2 permeation of 1444.68 barrer for a CO2 / CH4 mixed gas, and a CO2 / CH4 selectivity of 36.87; the carbon capture material containing a metal π site structure has a good application in carbon capture and can be used to separate CO2 / CH4.
[0057] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A MOF filling material with metal π sites, characterized in that: The MOF with metal π sites synthesized a series of MOF-808 (Mx-MOF-808) fillers containing unsaturated Zr sites by competitive coordination replacement method; the material has metal π sites, and the metal π site density is M 50 -MOF-808>M 30 -MOF-808>M 10 -MOF-808.
2. The M having a metal π site structure according to claim 1 x -MOF-808 preparation method, characterized in that, include: S1. Zirconium oxychloride octahydrate (ZrOCl2·8H2O), trimesic acid (H3BTC), and benzoic acid (HBC) in different molar ratios (10%, 30%, and 50%) were added to a Teflon-lined reactor (100 mL) to replace an equal amount of H3BTC. During the synthesis, HBC competes as a temporary ligand for coordination with the Zr cluster. Then a mixed solvent of N,N-dimethylformamide (DMF) / formic acid (HCOOH) was added. Next, the reactor was sealed and stirred for 0.5 hours to obtain a uniform mixed solution. The reactor was then transferred to a drying oven in an oven and kept at a certain temperature for several hours. After cooling to room temperature, the reaction product was washed with DMF and MeOH and centrifuged to separate the white precipitate. Then, the solid product was immersed in methanol (MeOH) for three days (MeOH was replaced every day), and a white precipitate was obtained after centrifugation. The white powder was obtained after being placed in a vacuum drying oven at 80°C overnight and named M x -MOF-808. The M having a metal π site structure x - A method for preparing MOF-808 material, characterized in that the M in step S1 x - In MOF-808, the dosage of ZrOCl2·8H2O, H3BTC and HBC is in the following relationship: 0.70-0.75g: 0.45-0.5g: 10-50%; In step S1, the volume ratio of DMF to HCOOH is 25-30 mL:25-30 mL. The experimental conditions in S1 were heating with stirring at 25-30°C for 0.5-1 h. The experimental conditions for immersing the product in methanol in S1 are 50-100 mL, displacing in methanol for 3-5 days, and heating and drying in an oven at 75-90°C for 24-30 hours.
3. The M having a metal π site structure according to claim 1 x -Application of MOF-808 materials in the preparation of carbon capture materials.
4. A method comprising the M having a metal π site structure as claimed in claim 1 x - A method for preparing a carbon capture material of MOF-808, characterized in that: The carbon capture material is the M having a metal π site structure as claimed in claim 1 x -MOF-808 material is a filler, polyether polyimide block Pebax is a polymer matrix, and the carbon capture material is formed by physically blending the filler and the polymer matrix at room temperature; the mass percentage of the filler in the carbon capture material is 1-15wt%. The thickness of the carbon capture material is 100-110μm.
5. Use of the carbon capture material according to claim 4 in CO2 capture.
Citation Information
Cited By
MOF-808-CA-Me mixed matrix gas separation membrane as well as preparation method and application thereof
CN120115030A